Endocrinal and autoimmune linkage: Evidences from a controlled study of subjects with polycystic ovarian syndrome - Sheetal Arora; Kiran Sinha; Sachin Kolte; Ashish Mandal (Wolters Kluwer Medknow Publications, 2016)
BACKGROUND: Polycystic ovary syndrome (PCOS) is a metabolic syndrome, characterized by anovulation, hyperandrogenism, and polycystic ovary. With serological markers of autoimmunity found elevated in PCOS, there is a possible link between autoimmunity and PCOS. AIM: The study aimed to investigate the possible correlation between autoimmune markers of autoimmune thyroiditis (AIT) and PCOS. SETTING AND DESIGN: This case control study was conducted at the Department of Pathology of a tertiary care academic center during a 1-year period. MATERIALS AND METHODS: Fifty-five subjects with clinical PCOS and 51 age matched control non-PCOS subjects were recruited and subjected to clinical, biochemical, and endocrinal evaluation for AIT. All subjects underwent blood glucose and serum sampling for luteinizing hormone (LH), follicle stimulating hormone (FSH), testosterone, dehydroepi androsterone, thyroxine, thyroid stimulating hormone, anti-thyroid peroxidase, anti-thyroglobulin (Tg), and insulin. STATISTICAL ANALYSIS: Statistical analysis was performed using SPSS version 12 for Windows. The quantitative variables are described as mean ± standard deviation. To compare quantitative variables between two groups, unpaired t-test was used. The Chi-square/Fischer's exact test was used to compare qualitative variables. ANOVA was used to compare the PCOS and non-PCOS groups. P < 0.05 was considered significant. RESULTS: Significantly higher prevalence of AIT (anti-Tg antibodies) was noted in subjects with PCOS as compared to non-PCOS control subjects (P < 0.05). The PCOS subjects had higher insulin resistance index and also twice the level of LH: FSH ratio as compared to controls. CONCLUSION: Higher prevalence of AIT in PCOS subjects suggest possible role of autoimmune phenomenon in the etiopathogenesis of PCOS. More data from longitudinal follow-up studies is required to clearly establish this possible link.